PENGARUH PENAMBAHAN SERAT POLYPROPYLENE TERHADAP KUAT TEKAN FOAM CONCRETE (Universitas Muhammadiyah Palembang, 2022)
Lightweight concrete has a specific gravity of 400 - 1,600 kg/m3 so it has a lower weight than normalconcrete. One type of lightweight concrete is foam concrete which is formed by adding air to the concretemixture. The compressive strength of foam concrete is still very low. With the addition of polypropylenefibers can increase the compressive strength of the concrete. The value of the compressive strength offoam concrete with a mixture of 0% polypropylene fiber shows a value of 2.85 MPa. The addition of 0.2%fiber showed a value of 7.77 MPa. The percentage of 0.4% polyoropylene fiber has a compressivestrength of 8.38 MPa.